Impacto del teletrabajo suplementario en la gestión de equipos en el área administrativa de la Empresa ACO (Alimentos al Consumidor de IRCC S.A.S PJ COL S.A.S Y L&C S.A) (2024)
This degree work analyzes the impact of supplementary teleworking in the Foods to the Consumer company (ACO), focusing on the administrative area and, specifically, Expansion management. ACO, responsible for the management of commercial chains such as El Corral, Corral Gourmet, Papa John's, Leños & Carbón, Beer Station, among others, ACO has implemented supplementary teleworking as part of its work practices. This study seeks to determine if this work modality has had a positive impact on team management and the fulfillment of organizational goals. The research is carried out using a quantitative methodology, implementing a survey of its employees, which covers crucial aspects such as communication, collaboration, job satisfaction, and general well-being since the implementation of supplementary teleworking in the organization.